2016
DOI: 10.3171/2016.6.jns152797
|View full text |Cite
|
Sign up to set email alerts
|

Association of collagen architecture with glioblastoma patient survival

Abstract: Objective Glioblastoma (GBM) is the most malignant primary brain tumor. Collagen is present in low amounts in normal brain, but in GBMs, collagen gene expression is reportedly upregulated. However, to the authors’ knowledge, direct visualization of collagen architecture has not been reported. The authors sought to perform the first direct visualization of GBM collagen architecture, identify clinically relevant collagen signatures, and link them to differential patient survival. Methods Second-harmonic genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 32 publications
(47 reference statements)
2
66
1
Order By: Relevance
“…Although collagen is present in only small amounts in the normal human brain, glioblastoma cells readily bind to collagen 20 . Moreover, recent studies have shown that fibrillar collagens are an integral part of the locally produced extracellular matrix in glioblastomas 21,22 , yet little is known about the traction forces exerted by GBM in order to facilitate movement through brain tissue. Furthermore, collagen is found in the basement membrane surrounding blood vessels, which are a major route of GBM invasion 20,23 .…”
Section: Mainmentioning
confidence: 99%
“…Although collagen is present in only small amounts in the normal human brain, glioblastoma cells readily bind to collagen 20 . Moreover, recent studies have shown that fibrillar collagens are an integral part of the locally produced extracellular matrix in glioblastomas 21,22 , yet little is known about the traction forces exerted by GBM in order to facilitate movement through brain tissue. Furthermore, collagen is found in the basement membrane surrounding blood vessels, which are a major route of GBM invasion 20,23 .…”
Section: Mainmentioning
confidence: 99%
“…4,5 Understanding which factors promote stemness and treatment resistance of glioma cells is of intense interest in developing new therapies in glioma. A large number of studies over the past decade have established that there is considerable plasticity in glioblastoma cell phenotypes, [6][7][8][9][10][11] that stem cell characteristics can be acquired by non-stem-like cells, 8,9,[12][13][14][15] and that microenvironmental cues such as hypoxia, 16 extracellular matrix proteins, [17][18][19][20][21][22][23][24][25] or growth factors secreted by stromal cells [26][27][28] may be sufficient to induce tumor cell stemness and therapeutic resistance. The role of the microenvironment in regulating tumor stemness is further supported by the finding that stem-like tumor cells are enriched in specific tumor niches; in GBM, primarily the perivascular niche (PVN) and hypoxic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to integrins, the receptor tyrosine kinase discoidin domain receptor 1 (DDR1) binds to and is activated by collagens in the ECM (Xu et al, 2012), which are expressed in brain tumors and are associated with patient prognosis (Huijbers et al, 2010;Pointer et al, 2017). Type I collagen (Col I) was shown to populate microenvironmental niches where GBM GSCs reside, survive treatment, and propagate into recurrence (Motegi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%